From Scent to Science: Aromatherapy as a Natural Approach in Pharmaceutics (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Aromatherapy refers to the therapeutic use of essential oils extracted from medicinal plants. It is increasingly being explored as a complementary approach in healthcare because of its potential role in promoting relaxation, reducing stress, and supporting symptom management. Objective this presentation, From Scent to Science: Integrating Aromatherapy into Modern Pharmacy, aims to highlight the scientific basis, clinical relevance, and pharmacy-based application of aromatherapy. Scientific Basis Essential oils contain bioactive compounds that may demonstrate antimicrobial, anti-inflammatory, analgesic, and anxiolytic properties. These effects suggest possible value in supportive care for conditions such as anxiety, pain, nausea, and sleep disturbances. Pharmacy Relevance In modern pharmacy, aromatherapy can be considered as an adjunct to conventional treatment. Its integration requires proper attention to dosage, formulation, quality control, and standardization to ensure safe and rational use. Conclusion Aromatherapy offers a promising bridge between traditional plant-based knowledge and modern pharmaceutical science. Further research and clinical validation are needed to establish its role in evidence-based pharmacy practice.
Keywords: Aromatherapy; essential oils; modern pharmacy; complementary therapy; safety; clinical integration